Anopheles gambiae Antiviral Immune Response to Systemic O'nyong-nyong Infection - Waldock, Joanna (Public Library of Science, 2012)
BACKGROUND: Mosquito-borne viral diseases cause significant burden in much of the developing world. Although host-virus interactions have been studied extensively in the vertebrate host, little is known about mosquito responses to viral infection. In contrast to mosquitoes of the Aedes and Culex genera, Anopheles gambiae, the principal vector of human malaria, naturally transmits very few arboviruses, the most important of which is O'nyong-nyong virus (ONNV). Here we have investigated the A. gambiae immune response to systemic ONNV infection using forward and reverse genetic approaches. METHODOLOGY/PRINCIPAL FINDINGS: We have used DNA microarrays to profile the transcriptional response of A. gambiae inoculated with ONNV and investigate the antiviral function of candidate genes through RNAi gene silencing assays. Our results demonstrate that A. gambiae responses to systemic viral infection involve genes covering all aspects of innate immunity including pathogen recognition, modulation of immune signalling, complement-mediated lysis/opsonisation and other immune effector mechanisms. Patterns of transcriptional regulation and co-infections of A. gambiae with ONNV and the rodent malaria parasite Plasmodium berghei suggest that hemolymph immune responses to viral infection are diverted away from melanisation. We show that four viral responsive genes encoding two putative recognition receptors, a galectin and an MD2-like receptor, and two effector lysozymes, function in limiting viral load. CONCLUSIONS/SIGNIFICANCE: This study is the first step in elucidating the antiviral mechanisms of A. gambiae mosquitoes, and has revealed interesting differences between A. gambiae and other invertebrates. Our data suggest that mechanisms employed by A. gambiae are distinct from described invertebrate antiviral immunity to date, and involve the complement-like branch of the humoral immune response, supressing the melanisation response that is prominent in anti-parasitic immunity. The antiviral immune response in A. gambiae is thus composed of some key conserved mechanisms to target viral infection such as RNAi but includes other diverse and possibly species-specific mechanisms.